Effects of treatment of dielectric barrier discharge cold plasma (DBD‐CP) on mechanical, barrier and functional characteristics of casein‐based films. (17th November 2021) - Hou, Yaqi; Liu, Qi; Mian, Safian Murad; Luo, Yanghe; Mu, Guangqing; Jiang, Shujuan; Zhou, Mingyi; Wu, Xiaomeng
Summary: Dielectric barrier discharge cold plasma (DBD‐CP) improves packing characters of films. According to our previous study, the physical performances including barrier and mechanical properties of casein films were enhanced by DBD‐CP treatment. The aim of this paper was to study the effects of DBD‐CP discharge on the physical performances of films made from casein‐based film‐forming solutions. The structural characteristics, mechanical and barrier properties, and heat stability of the produced casein films were evaluated. As expected, the differential scanning calorimeter (DSC) results indicated that the DBD‐CP treatment improved heat stability of the films. However, other properties such as tensile strength (TS), elongation at break (EAB) and barrier to water vapours were negatively affected. Similar results were obtained after examining casein film‐forming solution treated with DBD‐CP using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and X‐ray diffraction (XRD). In conclusion, treating the film‐forming solution directly with DBD‐CP should be done cautiously while reinforcing the films packing properties. Abstract : As expected, dielectric barrier discharge cold plasma (DBD‐CP) could facilitate the heat stability of films made from the treating casein solution. However, the properties, including tensile strength, elongation at break and barrier to water vapour of these films were reduced due to DBD‐CP changing the structure of casein in solution.